Specific Private Law Instruments of Financing In Vitro Fertilization Procedure - Marjanski, Vladimir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
The paper explains basic ways of functioning of private law instruments aimed at financing in vitro fertilization, expansion of which goes hand to hand with the progress of reproductive medicine. In addition to state (public) instruments of financing the costs of in vitro fertilization (IVF) procedure, comparative practice has experienced a development of private law instruments for covering such expenses. These instruments are offered by insurance companies, other financial organizations (funds which are established with particular purpose) or clinics (often consortium of clinics) which practice in vitro fertilization. The most common among them are: 1. Private health insurance which covers the expenses incurred in connection to IVF procedure; 2. The program of refund (return) of most (80 to 90 percent) or all (100 percent) of the expenses of IVF after a number of unsuccessful procedures (known under different titles such as: money-back guarantee program, shared-risk, success-based risk sharing plan, IVF success guarantee program, the IVF baby guarantee or your money back plan, pregnancy guarantee program etc. ); 3. Packages contained of a number of procedures – cycles for lower price (packages of 2, 3 or 4 ivf cycles). Programs such as these increase the level of reproductive medicine’s usability. Since the programs are not yet applied in Serbia, the paper explains basic mechanisms of their functioning in comparative law.
Keywords: insurance from risk of failure of the IVF procedure; private health insurance of costs incurred by the IVF procedure; private financing of IVF expenses; In vitro fertilization (IVF)